Association between Central Retinal Vein Occlusion and Mental Health Disorders - Shushtarian, Seyed Mohammad Masoud; Eslami Vaghar , Mohammad (Journal of Ophthalmic and Optometric Sciences, 2025)
Purpose: To investigate the association between central retinal vein occlusion (CRVO) and the presence of mental health disorders. Patients and Methods: This observational study included 120 patients with CRVO, aged 48–82 years. Psychiatric assessment was performed using standardized tools, including the Beck Anxiety Inventory (BAI) and the Beck Depression Inventory (BDI), to evaluate the prevalence of depression, anxiety, and related mental health disorders. Results: Of the 120 patients, 71 (59.16 %) were diagnosed with mental health disorders, most commonly depression and anxiety. The findings indicate that more than half of patients with CRVO experience significant psychiatric comorbidities. Conclusion: Mental health disorders, particularly depression and anxiety, are highly prevalent in patients with CRVO. These results underscore the need for routine psychiatric evaluation and integrated care strategies to improve overall outcomes in affected individuals.